Aluminum alloy surface micro-arc oxidation-plasma diffusion coating obdurability coating and preparation method

By performing plasma penetration in the microarc oxidized ceramic layer of aluminum alloy, a dense nickel penetration layer is formed, which solves the structural failure problems caused by the brittleness of the ceramic coating and the porous structure, and significantly improves the strength and stress resistance of the coating.

CN119776948AInactive Publication Date: 2025-04-08东方电气长三角(杭州)创新研究院有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411840625.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The aluminum alloy microarc oxidized ceramic coating has a brittle and porous structure, which is prone to cracking and peeling under stress conditions, resulting in structural failure.

Method used

Plasma seepage plating technology is used to form a dense seepage plating layer in the micro-arc oxidized ceramic layer, and metal nickel is used for seepage plating to enhance the bonding force and stress peeling resistance of the coating.

Benefits of technology

It significantly improves the strength and toughness of the aluminum alloy surface coating, enhances the stress resistance of the ceramic composite coating, and reduces peeling and cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776948A_ABST
    Figure CN119776948A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum alloy surface micro-arc oxidation-plasma diffusion coating obdurability coating and a preparation method, the aluminum alloy surface micro-arc oxidation-plasma diffusion coating composite coating comprises a micro-arc oxidation ceramic layer and a plasma diffusion coating, firstly, aluminum alloy is subjected to micro-arc oxidation treatment in a sodium silicate electrolyte; and then nickel is plated on the surface of the ceramic layer through the plasma diffusion plating technology, the filling and hole sealing effects on the loose ceramic layer are achieved, the obdurability of the porous ceramic layer can be effectively improved, and the binding force and the stress stripping resisting effect of the ceramic layer can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface modification, and particularly relates to a micro-arc oxidation-plasma permeation coating on the surface of an aluminum alloy and a preparation method thereof. Background Art

[0002] Aluminum alloys have significant advantages such as high specific strength, excellent casting properties, high plastic processing properties and weldability, and have been widely used in transportation industries such as automobile manufacturing and aerospace. However, the corrosion potential of aluminum alloys under natural conditions is low, resulting in its lack of corrosion resistance, which restricts its application in practical engineering.

[0003] Micro-arc oxidation is an electrochemical process that uses electrical parameters to cause arc discharge on the substrate surface in a specific electrolyte environment. After a series of complex interactions of electrochemistry, thermochemistry and plasma chemistry, a ceramic coating mainly composed of substrate metal oxides is grown in situ on the metal substrate. Micro-arc oxidation technology is widely used in material surface treatment and is currently an important technology in the field of aluminum alloy surface modification.

[0004] However, the micro-arc oxidation ceramic layer has a brittle porous structure, which is composed of a dense layer at the membrane base and a loose layer on the outside. It is prone to cracking and peeling, and is prone to structural failure under stress conditions. Summary of the invention

[0005] The purpose of the present invention is to enhance the toughness of aluminum alloy micro-arc oxidation ceramic coating, and to provide an aluminum alloy surface micro-arc oxidation-plasma permeation strong and tough coating and a preparation method thereof.

[0006] In order to achieve the above objectives, the present invention adopts the following technical scheme: as a first aspect, a micro-arc oxidation-plasma diffusion plating toughness coating on the surface of an aluminum alloy is provided, wherein the micro-arc oxidation-plasma diffusion plating composite coating on the surface of the aluminum alloy comprises, from bottom to top, a porous micro-arc oxidation ceramic layer and a plasma diffusion plating layer covering the aluminum alloy; the plasma diffusion plating layer adopts metallic nickel.

[0007] Furthermore, the porous micro-arc oxidation ceramic layer includes, from bottom to top, a micro-arc oxidation dense layer and a micro-arc oxidation loose layer diffused with metallic nickel, the thickness of the micro-arc oxidation dense layer and the micro-arc oxidation loose layer are both 5 to 10 μm, the thickness of the plasma diffusion layer is 2 to 5 μm, and the grain size of nickel in the plasma diffusion layer is 5 μm.

[0008] As a second aspect, the present invention provides a method for preparing a micro-arc oxidation-plasma permeation toughness coating on the surface of an aluminum alloy, comprising the following steps:

[0009] (1) using a sodium silicate electrolyte to perform micro-arc oxidation treatment on the aluminum alloy after surface cleaning to prepare an aluminum alloy with a porous micro-arc oxidation ceramic layer on the surface;

[0010] (2) cleaning the aluminum alloy having the porous micro-arc oxidation ceramic layer on the surface, drying it, and performing surface plasma cleaning in an argon environment;

[0011] (3) In an argon environment, the aluminum alloy after surface plasma cleaning is subjected to plasma nickel plating treatment; after completion, the aluminum alloy is cooled to below 60° C. and taken out to obtain a micro-arc oxidation-plasma permeation and toughening composite coating on the aluminum alloy surface.

[0012] Furthermore, in step (1), the final concentrations of the components in the sodium silicate electrolyte are: 10 g / L sodium silicate, 1 g / L sodium hydroxide, and 0.5 g / L sodium fluoride. The electrolyte is mixed and dissolved with a glass rod and allowed to stand for more than 30 minutes to obtain the electrolyte.

[0013] Furthermore, in step (1), the micro-arc oxidation treatment is specifically as follows: immersing the aluminum alloy in a sodium silicate electrolyte and connecting the positive electrode of the power supply, and connecting the stainless steel electrolytic cell to the negative electrode of the power supply, wherein the electrical parameters are: frequency 200 Hz, duty cycle 40%, voltage 460-500 V, and treatment time 20 min.

[0014] Furthermore, in step (2), the cleaning is: ultrasonic cleaning in anhydrous ethanol for 3 minutes; the drying is: drying in a vacuum tube furnace; the surface plasma cleaning in an argon environment is specifically: clamping the cleaned and dried aluminum alloy in the sample position in the plasma equipment chamber, and evacuating the plasma equipment chamber to a vacuum degree of 5×10 -3 After Pa, high-purity argon gas with a purity of 99.99% was introduced, and the argon gas flow rate was set to 200-300 sccm, and the surface plasma cleaning was carried out for 10 minutes.

[0015] Furthermore, in an argon environment, the aluminum alloy after surface plasma cleaning was subjected to plasma nickel plating as follows: a nickel target with a purity of 99.95% was used as the target material, the aluminum alloy sample after surface plasma cleaning was fixed parallel to the target material, the inter-electrode spacing was 10 mm, the chamber gas was 99.99% high-purity argon gas, the gas pressure was 30 Pa, the working voltage of the aluminum alloy sample was 400 V, the target voltage was 700 V, the target current was 2 A, and the coating time was 1 h.

[0016] Furthermore, the aluminum alloy is 5052 aluminum alloy, and its element composition is Si 0.25%, Fe 0.40%, Cu 0.10%, Mn 0.10%, Mg 0.22%-0.28%, Cr 0.15-0.35%, Zn 0.10%, and the balance is Al.

[0017] Furthermore, in step (1), the composition of the prepared porous micro-arc oxidation ceramic layer is: 60 vol% Al 2 O 3 , 30 vol% AlSiO 3, 10 vol% SiO 2 , and trace amounts of elemental Al.

[0018] Furthermore, in step (1), the porous micro-arc oxidation ceramic layer obtained has a melting point of 1200° C., a thickness of 10 to 20 μm, a pore size of 5 to 10 μm, and a porosity of 5 to 10%.

[0019] Compared with the prior art, the advantages of the present invention are: due to the prominent brittle nature of the micro-arc oxidation ceramic layer and its poor stress resistance, a dense infiltration layer is formed in the micro-arc oxidation loose layer through plasma infiltration, which significantly enhances the strength and toughness of the surface coating, and has important technical significance in the field of strengthening and toughening modification of ceramic composite coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 1 and 2 are hardness test morphology diagrams of the embodiments of the present invention; wherein, (A) is the hardness test morphology diagram of embodiment 1; and (B) is the hardness test morphology diagram of embodiment 2. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with embodiments and drawings.

[0022] Embodiment 1~3:

[0023] The specific preparation process includes:

[0024] (1) Wire cutting was used to cut 2 mm thick 5052 aluminum alloy sheets into samples with a size of 30 × 30 × 2 mm. At the same time, in order to facilitate the preparation of subsequent micro-arc oxidation samples, a hole with a diameter of 2 mm was processed on the width edge of the sample. The surface of the cut sample was polished flat with 320# to 2000# SiC sandpaper to remove surface defects. Then, anhydrous ethanol was used for ultrasonic cleaning for 3 minutes, and finally the sample was blown dry and bagged for later use.

[0025] (2) Add 40g of sodium silicate, 2g of sodium fluoride and 4g of sodium hydroxide to 4L of deionized water, stir evenly with a glass rod until all dissolved without precipitation, and then let it stand for 1 hour until the electrolyte stabilizes. Fix the aluminum alloy sample with a 2mm aluminum wire and a clamping device, and connect it to the positive electrode of the micro-arc oxidation power supply. The sample is immersed in the electrolyte as the anode, and the aluminum wire is wrapped with a thermoplastic tube to prevent the micro-arc oxidation reaction from affecting the stability of the sample coating. Use a stainless steel barrel as an electrolytic cell to carry the electrolyte, and connect it to the negative electrode of the power supply, which serves as the cathode in the experiment. Connect the interlayer of the electrolytic cell to the cooling water pool. During the experiment, the cooling water circulates and keeps the electrolyte temperature below 60°C.

[0026] (3) The electrical parameters of micro-arc oxidation are: voltage 460-500V, power frequency 200Hz, duty cycle 40%, treatment time 20min. After the preparation, the sample is taken out, washed with deionized water, and then ultrasonically cleaned with anhydrous ethanol for 3min. Finally, it is dried in a vacuum tube furnace and bagged for use. The voltage of micro-arc oxidation in Example 1 and Example 2 is 460V, and the voltage of micro-arc oxidation in Example 3 is 500V.

[0027] (4) Plasma cleaning is performed on the surface of the aluminum alloy covered with the ceramic layer; the plasma equipment chamber is evacuated to a vacuum degree of 5×10 -3 After 300 Pa, high-purity argon gas was introduced for 10 min.

[0028] (5) Install the nickel target on the target position of the plasma equipment, install the aluminum alloy after micro-arc oxidation treatment on the sample table of the plasma equipment, and place and fix the nickel target and the aluminum alloy sample in parallel. Plasma infiltration plating is performed on the debugged sample. The source voltage of the nickel target is 700V, the working voltage of the aluminum alloy substrate is 400V, the distance between the nickel target and the substrate is 10mm, the argon gas pressure in the preparation process is 30Pa, and the working time is 1h. Example 1 does not perform plasma infiltration plating, and Examples 2 and 3 perform plasma infiltration plating according to the above parameters.

[0029] The ceramic coating obtained by micro-arc oxidation has obvious loose and porous properties. When the substrate is under stress, it is easy to peel off and crack, causing structural failure of the ceramic layer. However, after the introduction of plasma permeation, on the one hand, the ceramic layer has a higher melting point and can serve as a transition layer between the permeated metal nickel and the substrate aluminum alloy, enhancing the bonding strength of the composite coating; on the other hand, the porous structure of the micro-arc oxidation ceramic layer can provide a permeation channel for the plasma process and form an interlocking structure.

[0030] The aluminum alloy micro-arc oxidation-plasma nickel infiltration layer prepared in this embodiment is obtained by preparing a porous micro-arc oxidation ceramic layer on an aluminum alloy, and then plasma infiltration nickel on the porous micro-arc oxidation ceramic layer. Nickel is infiltrated on the surface of the ceramic layer to fill and seal the loose ceramic layer, which can effectively improve the toughness of the porous ceramic layer, and enhance the bonding force and stress-stripping resistance of the ceramic layer. The plasma infiltration layer is a deposition layer located on the surface of the porous micro-arc oxidation ceramic coating, and the diffusion layer diffused into the porous micro-arc oxidation ceramic coating is called a micro-arc oxidation loose layer. Structurally, it is divided from bottom to top: the thickness of the micro-arc oxidation dense layer is 5 to 10 μm, the thickness of the micro-arc oxidation loose layer is 5 to 10 μm, and the thickness of the plasma infiltration layer is 2 to 5 μm.

[0031] The thickness of the permeation layer is affected by the structure of the micro-arc oxidation ceramic layer and the plasma parameters. The present invention adopts a constant voltage mode for micro-arc oxidation treatment. During discharge in the later stage of the reaction, due to the growth of the ceramic layer, the material resistance continues to increase, the surface discharge current continues to decrease, and the loose layer can maintain a relatively gentle structural growth, reducing the generation of cracks and large pores.

[0032] The performance of plasma plating mainly depends on its process parameters: source voltage, workpiece voltage, inter-electrode spacing, shielding gas pressure, and plating time. The main function of the source voltage is to control the ion bombardment energy and density on the source surface, thereby controlling the nickel supply of the source; the workpiece voltage affects the bombardment of ions on the workpiece surface; the inter-electrode spacing affects the utilization rate of the target element during the bombardment process; the shielding gas pressure affects the transport capacity and bombardment density of the target element during bombardment; and the plating time directly affects the thickness of the plating layer and the deposited layer.

[0033] In order to obtain a good composite coating, the melting point of the micro-arc oxidation ceramic layer should be between the aluminum alloy substrate and the infiltration material. If the pore size and the thickness of the loose layer are too small, it will affect the bonding strength of the composite coating, while if they are too large, the coating strength will be reduced.

[0034] Detection method of dense layer, permeation layer and deposition layer: Cut the sample by wire cutting, polish it with 320#~2000# SiC sandpaper to remove surface defects, then use anhydrous ethanol ultrasonic cleaning for 3 minutes after polishing, place it under a scanning electron microscope, and use secondary electron observation and measurement to obtain it.

[0035] Coating toughness test method: Use wire cutting to cut a 10*10mm complete sample surface from the coated aluminum alloy, use resin to flatten the sample, expose the test surface, use anhydrous ethanol ultrasonic cleaning for 3 minutes, and use a vacuum tube furnace to dry. Use a Vickers hardness tester to test the hardness with a test force of 100gf. After obtaining the hardness, the toughness of the coating is determined by observing the cracks around the hardness test pit.

[0036] The embodiments of the present invention are shown in Table 1. The surface hardness of the aluminum alloy micro-arc oxidation-plasma diffusion plating composite coating prepared by the present invention is improved.

[0037] The toughness analysis of the coatings in Example 1 and Example 2 is as follows: Figure 1 As shown, the aluminum alloy micro-arc oxidation-plasma diffusion plating composite coating prepared by the present invention has significantly fewer cracks around the indentation after hardness test than the single aluminum alloy micro-arc oxidation coating, and its toughness is significantly improved.

[0038] Table 1: Performance test results of the embodiments of the present invention

[0039]

[0040] It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Without making creative work, any modification, equivalent replacement, improvement, etc., shall be included in the protection scope of the present invention.

Claims

1. A micro-arc oxidation-plasma permeation coating on the surface of an aluminum alloy, characterized in that: The aluminum alloy surface micro-arc oxidation-plasma infiltration composite coating comprises, from bottom to top, a porous micro-arc oxidation ceramic layer and a plasma infiltration layer covering the aluminum alloy; the plasma infiltration layer adopts metal nickel.

2. The aluminum alloy surface micro-arc oxidation-plasma permeation toughness coating according to claim 1 is characterized in that: The porous micro-arc oxidation ceramic layer includes a micro-arc oxidation dense layer and a micro-arc oxidation loose layer diffused with metallic nickel from bottom to top. The thickness of the micro-arc oxidation dense layer and the micro-arc oxidation loose layer are both 5-10 μm, the thickness of the plasma diffusion layer is 2-5 μm, and the grain size of nickel in the plasma diffusion layer is 5 μm.

3. A method for preparing a tough coating on an aluminum alloy surface by micro-arc oxidation-plasma permeation plating according to claim 1, characterized in that: The following steps are involved: (1) using a sodium silicate electrolyte to perform micro-arc oxidation treatment on the aluminum alloy after surface cleaning to prepare an aluminum alloy with a porous micro-arc oxidation ceramic layer on the surface; (2) cleaning the aluminum alloy having the porous micro-arc oxidation ceramic layer on the surface, drying it, and performing surface plasma cleaning in an argon environment; (3) In an argon environment, the aluminum alloy after surface plasma cleaning is subjected to plasma nickel plating treatment; after completion, the aluminum alloy is cooled to below 60° C. and taken out to obtain a micro-arc oxidation-plasma permeation and toughening composite coating on the aluminum alloy surface.

4. The method for preparing a tough coating on an aluminum alloy surface by micro-arc oxidation-plasma diffusion plating according to claim 3, characterized in that: In step (1), the final concentrations of the components in the sodium silicate electrolyte are: 10 g / L sodium silicate, 1 g / L sodium hydroxide, and 0.5 g / L sodium fluoride. The electrolyte is mixed and dissolved with a glass rod and allowed to stand for more than 30 minutes to obtain the electrolyte.

5. The method for preparing a tough coating on an aluminum alloy surface by micro-arc oxidation-plasma diffusion plating according to claim 3, characterized in that: In step (1), the micro-arc oxidation treatment is specifically as follows: immersing the aluminum alloy in a sodium silicate electrolyte and connecting the positive electrode of the power supply, and connecting the stainless steel electrolytic cell to the negative electrode of the power supply, wherein the electrical parameters are: frequency 200 Hz, duty cycle 40%, voltage 460-500 V, and treatment time 20 min.

6. The method for preparing a tough coating on the surface of an aluminum alloy by micro-arc oxidation-plasma diffusion plating according to claim 3, characterized in that: In step (2), the cleaning is: ultrasonic cleaning in anhydrous ethanol for 3 minutes; the drying is: drying in a vacuum tube furnace; the surface plasma cleaning in an argon environment is specifically: clamping the cleaned and dried aluminum alloy in the sample position in the plasma equipment chamber, and evacuating the plasma equipment chamber to a vacuum degree of 5×10 -3 After Pa, high-purity argon gas with a purity of 99.99% was introduced, and the argon gas flow rate was set to 200-300 sccm, and the surface plasma cleaning was carried out for 10 minutes.

7. The method for preparing a tough coating on an aluminum alloy surface by micro-arc oxidation-plasma diffusion plating according to claim 3, characterized in that: In an argon environment, the aluminum alloy after surface plasma cleaning is subjected to plasma nickel plating as follows: a nickel target with a purity of 99.95% is used as the target material, the aluminum alloy sample after surface plasma cleaning is fixed parallel to the target material, the inter-electrode spacing is 10 mm, the chamber gas is 99.99% high-purity argon gas, the gas pressure is 30 Pa, the working voltage of the aluminum alloy sample is 400 V, the target voltage is 700 V, the target current is 2 A, and the coating time is 1 h.

8. The method for preparing a tough coating on the surface of an aluminum alloy by micro-arc oxidation-plasma permeation plating according to claim 3, characterized in that: The aluminum alloy is 5052 aluminum alloy, and its element composition is Si 0.25%, Fe 0.40%, Cu 0.10%, Mn 0.10%, Mg 0.22%-0.28%, Cr 0.15-0.35%, Zn 0.10%, and the balance is Al.

9. The method for preparing a tough coating on the surface of an aluminum alloy by micro-arc oxidation-plasma diffusion plating according to claim 3, characterized in that: In step (1), the composition of the prepared porous micro-arc oxidation ceramic layer is: 60 vol% Al2O3, 30 vol% AlSiO3, 10 vol% SiO2, and a trace amount of elemental Al.

10. The method for preparing a tough coating on the surface of an aluminum alloy by micro-arc oxidation-plasma diffusion plating according to claim 3, characterized in that: In step (1), the porous micro-arc oxidation ceramic layer obtained has a melting point of 1200° C., a thickness of 10 to 20 μm, a pore size of 5 to 10 μm, and a porosity of 5 to 10%.

Citation Information

Patent Citations

  • Preparation method of light metal and alloy surface composite coating thereof

    CN103882426A

  • Preparation method for aluminum alloy micro-arc oxidation-electroless nickel-plating composite coating

    CN107460515A

  • Aluminum alloy surface micro-arc oxidation anti-wear composite coating and preparation method thereof

    CN111647925A

  • Method for preparing tantalum biological coating on surfaces of magnesium and magnesium alloy

    CN114381778A

  • Aluminum alloy surface treatment process

    CN114752981A